Demografi dan Kompetensi Pengembangan Instrumen Penilaian Hasil Belajar Berbasis Higher Order Thinking Skills Guru Ilmu Pengetahuan Sosial - Wahidmurni, Wahidmurni; Yuniar, Marandy Setyo; Zuhrotul, Hani’ah (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
The research aims to investigate: (1) the content of higher-order thinking skills (HOTS) in basic competence verbs and learning assessment instruments prepared by teachers, (2) the aspect of demography and teacher competency in developing HOTSbased learning assessment instrument, and (3) teacher’s problems in developing HOTS based learning assessment instrument. To accomplish the aims, the researchers employed a mixed-method approach and Convergence Model design. The data collection involves interviews with teachers, documentation and questionnaire. Quantitative data were analyzed using percentage technique. Meanwhile, the qualitative ones were analyzed using condensation patterns, data presentation, and conclusion drawing. The result of the research shows that: (1) Most of the basic competence verbs in the curriculum of social studies subject contain HOTS, but only a few of HOTS-based assessment instruments are employed, (2) demographically, most teachers have an irrelevant educational background and have not been trained before. Even though most of them are professional teachers, their understanding and competencies in developing HOTS-based assessment instruments are still low, and (3) the main problem faced by teachers is their incompetence in developing basic competency verbs into suitable operational verbs of social studies. It indicates the urgency of assistance and training for teachers to improve their competencies in developing this instrument.